Pandangan Hidup dan Simbol-Simbol Dalam Budaya Jawa - M. Muslich (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2004)
Javanese Society is unity bounded by the norm of life, that of tradition and religion. The fundamental characteristic of it is having dynamic, tolerant, acomodative and optimistic religiousity spirit. This can be proved by several classical documents, Serat-serat Piwulang written by some authors in the renaisance era of modern Javanese Letters like Serat Wulangreh, Serat Suluk Cipta Waskitha, Serat Suluk Haspiya, Serat Wedhatama, Serat Centhini, and Serat Wirit Hidayat Jati etc.. These documents are needed investigating for understanding the construction of Javanese culture. The classical texts are not narration living in the vacuum history, space and time. On contrary, they are the variables and values those must be explained in its era context. So, the understanding of Javanese culture articulation in many Serat Piwulang of Java gives some special uniqueness in understanding the Javanese culture.